2016
DOI: 10.1016/j.foodchem.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Pectin content and composition from different food waste streams

Abstract: In the present paper, 26 food waste streams were selected according to their exploitation potential and investigated in terms of pectin content. The isolated pectin, subdivided into calcium bound and alkaline extractable pectin, was fully characterized in terms of uronic acid and other sugar composition, methylation and acetylation degree. It was shown that many waste streams can be a valuable source of pectin, but also that pectin structures present a huge structural diversity, resulting in a broad range of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
4
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(107 citation statements)
references
References 39 publications
6
90
4
7
Order By: Relevance
“…The results showed that the structure of the pectin extracted from wastes is similar to that from the raw matrices, although the methylation and acetylation degrees are lower due to the processing and/or enzymatic actions. The collected data also emphasise the potential of the recovered pectin to be used either as food additives or other applications (if the minimum concentration in galacturonic acid is not reached) [63].…”
Section: Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the structure of the pectin extracted from wastes is similar to that from the raw matrices, although the methylation and acetylation degrees are lower due to the processing and/or enzymatic actions. The collected data also emphasise the potential of the recovered pectin to be used either as food additives or other applications (if the minimum concentration in galacturonic acid is not reached) [63].…”
Section: Polysaccharidesmentioning
confidence: 99%
“…essential for food industry. According to the Joint Food and Agriculture Organization/World Health Organization (FAO/WHO) Expert Committee on Food Additives and the European Commission, a pectic polysaccharide must have a content of minimum 65% in galacturonic acid [60][61][62][63]. Wastes such as orange peels or apple pomace are well-known sources of pectins, but there are also other waste streams that can be exploited in this sense.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Pectins are also naturally occurring heteropolysaccharides in native wood found in the primary cell walls, secondary cell walls, and the middle lamella . Tokareva et al.…”
Section: Lignocellulosic Secondary Ion Peaksmentioning
confidence: 99%
“…As an example, around 70% of the worldwide production of oranges is intended for the juice industry generating about 50% by weight of residues, mainly composed of skins (flavedo and albedo), pulp, and seeds . These by‐products are rich in phenolic compounds, essential oils, pigments and, in particular, cell wall polysaccharides such as pectins, hemicelluloses and cellulose …”
Section: Introductionmentioning
confidence: 99%